Analisis Kritis Terhadap Buku Filsafat Pendidikan Islam Karya Muhammad As Said - Seka Andrean; Mahmud Arif (Institut Agama Islam Negeri Palopo, 2020)
Islamic education has been considered the number two education of public education. Starting from aspects of the quality of education to the funding of education itself. In this paper the author analyzes critically the book of Islamic education philosophy by Muhammad As Said. The results of the analysis showed that the book of Islamic education philosophy by Muhammad As Said, did not explain clearly the origin of the philosophy of Islamic education. In the book, it cites and discusses the philosophy of western education. This book also explains that general philosophy has a very close relationship with the philosophy of education because education is the executor of philosophical views and rules in the field of humanitarian experience called education. However, it is not explained the relationship between Islamic philosophy and Islamic education philosophy and has not been clearly seen the basic framework of islamic education philosophy building. The content of the book also discusses more common philosophical issues such as idealism, neoskolatism realism, pragmatism, and existentialism.